Histological evaluation in ulcerative colitis - DeRoche, Tom C. (Oxford University Press, 2014)
This review summarizes diagnostic problems, challenges and advances in ulcerative colitis (UC). It emphasizes that, although histopathological examination plays a major role in the diagnosis and management of UC, it should always be interpreted in the context of clinical, endoscopic, and radiological findings. Accurate diagnosis requires knowledge of the classic morphological features of UC, as well as a number of atypical pathological presentations that may cause mis-classification of the disease process, either in resection or biopsy specimens. These atypical pathological presentations include rectal sparing and patchiness of disease at initial presentation of UC in pediatric patients or in the setting of medically treated UC, cecal or ascending colon inflammation in left-sided UC, and backwash ileitis in patients with severe ulcerative pancolitis. Loosely formed microgranulomas, with pale foamy histiocytes adjacent to a damaged crypt or eroded surface, should not be interpreted as evidence of Crohn’s disease. Indeterminate colitis should only be used in colectomy specimens as a provisional pathological diagnosis. Patients with UC are at risk for the development of dysplasia and carcinoma; optimal outcomes in UC surveillance programs require familiarity with the diagnostic criteria and challenges relating to UC-associated dysplasia and malignancy. Colon biopsy from UC patients should always be evaluated for dysplasia based on cytological and architectural abnormalities. Accurate interpretation and classification of dysplasia in colon biopsy from UC patients as sporadic adenoma or UC-related dysplasia [flat, adenoma-like, or dysplasia-associated lesion or mass (DALM)] requires clinical and endoscopic correlation. Isolated polypoid dysplastic lesions are considered to be sporadic adenoma if occurring outside areas of histologically proven colitis, or adenoma-like dysplasia if occurring in the diseased segment. Recent data suggest that such lesions may be treated adequately by polypectomy in the absence of flat dysplasia in the patient. UC patients with DALM or flat high-grade dysplasia should be treated by colectomy because of the high probability of adenocarcinoma. The natural history of low-grade dysplasia (LGD) is more controversial: while multifocal LGD, particularly if detected at the time of initial endoscopic examination, is treated with colectomy, unifocal flat LGD detected during surveillance may be managed by close follow-up with increased surveillance. The surveillance interval and treatment options for UC patients with dysplasia are reviewed in detail.